Mindful Eating, Body Esteem, and Quality of Life among Young Adults: A Comparative Study - Adiba Khursheed; Dr. Chhayya Gupta (International Journal of Indian Psychȯlogy, 2025)
In today’s health-conscious and appearance-conscious world, it is more crucial than ever to comprehend how young adults view their bodies, eating patterns, and level of satisfaction in life. The current study explores the relationship between body esteem, mindful eating, and quality of life (QoL) among young adults (males and females). The sample consisted of 120 participants (60 males and 60 females) aged 25 to 35 years, selected through convenience sampling. A cross-sectional research design was used, and data were collected using three standardized tools: the Mindful Eating Questionnaire (MEQ), the Body-Esteem Scale for Adolescents and Adults (BESAA), and the WHO Quality of Life-BREF (WHOQOL-BREF). There was a significant gender difference in Quality of Life, with males having slightly higher scores than females, but not for mindful eating and body esteem. A significant negative correlation between mindful eating and body esteem and a highly significant positive correlation between body esteem and Quality of Life were found. Body esteem was a strong and significant predictor of QoL, whereas mindful eating was not. No significant gender difference was found in the domains of body esteem, whereas a significant age difference was found only in the disinhibition domain of mindful eating, with males scoring higher than females.